Elective Tracheostomy in COVID-19 Patients: A Retrospective Case Series - Dias-Vaz, Marta; Tiago, Catarina; Morais, Ana; Ferreira, Milene; Carvalho, Filipa (Journal of the Portuguese Society of Anesthesiology, 2020)
The COVID-19 outbreak represents a global health threat due to the unprecedented number of patients admitted to intensive care units and the overwhelming need for mechanical ventilation. Performing a tracheostomy in COVID-19 patients represents a risk for patients and healthcare workers. We report a case series of 10 patients with COVID-19 who underwent elective open tracheostomies in a negative pressure operating room, carried out by an experienced multidisciplinary team. They were tracheostomized after a mean intubation period of 18.6 days (range, 13-23 days). Only one patient developed postoperative complications and no viral transmission to health care workers was documented. Hence, our experience supports the safety of tracheostomy in COVID-19 patients, provided that meticulous planning and strict safety recommendations are followed.